The Northern Sea Route in the 2010s: Development and Implementation of Relevant Law - Solski, Jan Jakub (Arctic Review on Law and Politics, 2020)
The 2010s was a busy decade for the Northern Sea Route (NSR). It started with the first shipping season to feature the international use of the NSR for commercial purposes, followed by a significant reform of the domestic legal regime, as well as the adoption of the Polar Code. The traffic has gradually picked up, and although the expectations of a significant surge in trans-Arctic navigation have not materialized, the NSR’s annual turnover has grown beyond the old records set by the USSR. While the Russian authorities have struggled to find the most optimal means of development of the NSR, the latter has recently been re-marketed as a Polar Silk Road, part of the grand Chinese One Belt One Road initiative. While Russia has been rebuilding its military presence in the Arctic, the French Navy vessel BSAH Rhone unexpectedly navigated through the NSR, inciting strong political, but yet not legal, response. The present article aims to take stock of the last decade, paying primary attention to the Russian State practice in developing, adopting, and enforcing legislation in the NSR. By describing the current status and identifying some of the regulatory trends, the article will draw cautious predictions on the role of the law of the sea in the management of the NSR in the near future.